2015
DOI: 10.1111/ijtd.12054
|View full text |Cite
|
Sign up to set email alerts
|

Social support at the workplace, motivation to transfer and training transfer: a multilevel indirect effects model

Abstract: Supervisor support, peer support and transfer motivation have been identified as important predictors of training transfer. Transfer motivation is thought to mediate the supporttraining transfer relationship. Especially after team training interventions that include all team members (i.e. whole-team training), individual perception of these factors might be shared among team members. However, an integration of the team level in the training transfer process is rare, yet still needed. Analyzing 194 employees fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
98
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 69 publications
(148 reference statements)
8
98
0
3
Order By: Relevance
“…Initial research results have confirmed motivation to transfer as a mediating factor between factors in the work environment as well as in the training design and training transfer. For example, supervisor support and peer support were found to influence training transfer indirectly, mediated through motivation to transfer (Massenberg & Kauffeld, ; Massenberg et al, ; Nijman & Gelissen, ; van den Bossche et al, ). Moreover, Grohmann et al () found motivation to transfer to act as a mediator between training design and training transfer.…”
Section: The Learning Transfer System and The Special Role Of Motivatmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial research results have confirmed motivation to transfer as a mediating factor between factors in the work environment as well as in the training design and training transfer. For example, supervisor support and peer support were found to influence training transfer indirectly, mediated through motivation to transfer (Massenberg & Kauffeld, ; Massenberg et al, ; Nijman & Gelissen, ; van den Bossche et al, ). Moreover, Grohmann et al () found motivation to transfer to act as a mediator between training design and training transfer.…”
Section: The Learning Transfer System and The Special Role Of Motivatmentioning
confidence: 99%
“…Compared to studies that have analyzed the influence of the learning transfer system before the training, many more studies have assessed the system and its influence on motivation to transfer after the training program (for an overview, see Gegenfurtner, Veermans, et al, 2009). Empirical results have shown that motivation to transfer is influenced by training‐specific as well as general factors related to the work environment (e.g., Axtell et al, ; Bates & Holton, ; Chiaburu, van Dam, & Hutchins, ; Foxon, ; Massenberg et al., ; Nijman & Gelissen, ; Seyler et al, ; van den Bossche et al, ), to the training design (e.g., Grohmann et al, ; Kauffeld et al, ; Ruona, Leimbach, Holton, & Bates, ), and to the trainee (e.g., Chiaburu et al, ; Naquin & Holton, ; Seyler et al, ). Table gives an overview of empirical results regarding the influencing factors in the learning transfer system on motivation to transfer after training programs.…”
Section: Learning Transfer System Factors Affecting Motivation To Tramentioning
confidence: 99%
See 1 more Smart Citation
“…Motivated employees are more engaged in their work (Rich 2006), their performance is of higher quality (Cerasoli et al 2014) and they profit more from occupational training (Massenberg et al 2015). Additionally, they are more strongly committed to their work, work longer hours, pick more challenging goals to achieve , and are more willing to share knowledge at the workplace (Lin 2007).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Past research has identified factors which influence the successful transfer of training (Bates et al ., ; Kauffeld et al ., ). For successful transfer of training, trainees’ motivation to transfer is a critical link (Gegenfurtner et al ., ; Grohmann et al ., ; Massenberg et al ., ). Motivation to transfer in turn is affected by several factors (for an overview, see Gegenfurtner et al ., ), including individual characteristics, organizational factors and training‐related characteristics.…”
Section: Introductionmentioning
confidence: 99%